2014
DOI: 10.1161/circulationaha.113.005457
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Global Epidemiology Study

Abstract: Background— Contemporary data from Western populations suggest steep declines in abdominal aortic aneurysm (AAA) mortality; however, international trends are unclear. This study aimed to investigate global AAA mortality trends and to analyze any association with common cardiovascular risk factors. Methods and Results— AAA mortality (1994–2010) using International Classification of Diseases codes were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(70 citation statements)
references
References 33 publications
2
67
0
1
Order By: Relevance
“…9 However, in a recent report, the same investigators found a very similar inverse association between body mass index and abdominal aortic aneurysms, 10 suggesting that this finding is reproducible. However, a causal explanation is elusive, so, for now, we may consider this to be yet another example of the apparent "obesity paradox.…”
Section: Article See P 2287mentioning
confidence: 85%
See 1 more Smart Citation
“…9 However, in a recent report, the same investigators found a very similar inverse association between body mass index and abdominal aortic aneurysms, 10 suggesting that this finding is reproducible. However, a causal explanation is elusive, so, for now, we may consider this to be yet another example of the apparent "obesity paradox.…”
Section: Article See P 2287mentioning
confidence: 85%
“…In fact, in contradistinction, in a cross-sectional population of subjects without known thoracic aortic disease, body mass index was positively associated with aortic root diameter. 9 However, in a recent report, the same investigators found a very similar inverse association between body mass index and abdominal aortic aneurysms, 10 suggesting that this finding is reproducible. However, a causal explanation is elusive, so, for now, we may consider this to be yet another example of the apparent "obesity paradox."…”
Section: Article See P 2287mentioning
confidence: 89%
“…AAA prevalence increases with age, and even though the incidence has declined in the past ten years [14], rupture of AAA is still a significant cause of death with 10–15% of AAAs presenting as ruptured AAAs (rAAA) in the emergency room. AAA rupture risk increases with increasing aortic diameter and this catastrophic event is associated with a mortality of 50 to 80% [1517].…”
Section: Clinical Studies On Aaamentioning
confidence: 99%
“…The risk of AAA rupture is determined by size; specifically, rupture occurs in approximately 2% of AAAs less than 4 cm in diameter and in more than 25% of AAAs larger than 5 cm. Surgical repair is indicated for large AAAs (diameter > 5.5 cm) or if the growth rate exceeds 1 cm/year [5]. …”
Section: Introductionmentioning
confidence: 99%